The signaling value of punishing norm-breakers and rewarding norm-followers - Fabrizio Adriani; Silvia Sonderegger (Games, 2018)
We formally explore the idea that punishment of norm-breakers may be a vehicle for the older generation to teach youngsters about social norms. We show that this signaling role provides sufficient incentives to sustain costly punishing behavior. People punish norm-breakers to pass information about past history to the younger generation. This creates a link between past, present, and future punishment. Information about the past is important for youngsters, because the past shapes the future. Reward-based mechanisms may also work and are welfare superior to punishment-based ones. However, reward-based mechanisms are fragile, since punishment is a more compelling signaling device (in a sense that we make precise).
Keywords: D82; D83; C72; 330; norms; punishment; reaward; signaling